THE PERCH-FISHERY BY SPECIAL TRAPS IN THE AREA AROUND MANDAPAM IN THE GULF OF MANNAR AND PALK BAY - Prabhu, M S (Indian Journal of Fisheries, 2016)
ONE of the indigenous methods of fishing prevalent in the Gulf of Mannarand Palk Bay is by the employment of traps, known locally by the name' Koodu'. These traps are primarily intended for catching percoid fisheswhich abound in localities with hard bottorn formed of rocks and coralscharacteristic of the inshore waters of the Gulf of Mannar and Palk Bay.As these areas are shallow, with rocks and corals scattered about, neithershore seines nor gill nets could be operated successfully in most of them,which probably explains the development of perch trapping in this part ofthe country as an organised fishery